The Radical S-Adenosyl-L-methionine Enzyme QhpD Catalyzes Sequential Formation of Intra-protein Sulfur-to-Methylene Carbon Thioether Bonds - Nakai, Tadashi; Ito, Hiroto; Kobayashi, Kazuo; Takahashi, Yasuhiro; Hori, Hiroshi; Tsubaki, Motonari; Tanizawa, Katsuyuki; Okajima, Toshihide (The Journal of biological chemistry, 2015)
The bacterial enzyme designated QhpD belongs to the radical S-adenosyl-L-methionine (SAM) superfamily of enzymes and participates in the post-translational processing of quinohemoprotein amine dehydrogenase. QhpD is essential for the formation of intra-protein thioether bonds within the small subunit (maturated QhpC) of quinohemoprotein amine dehydrogenase. We overproduced QhpD from Paracoccus denitrificans as a stable complex with its substrate QhpC, carrying the 28-residue leader peptide that is essential for the complex formation. Absorption and electron paramagnetic resonance spectra together with the analyses of iron and sulfur contents suggested the presence of multiple (likely three) [4Fe-4S] clusters in the purified and reconstituted QhpD. In the presence of a reducing agent (sodium dithionite), QhpD catalyzed the multiple-turnover reaction of reductive cleavage of SAM into methionine and 5'-deoxyadenosine and also the single-turnover reaction of intra-protein sulfur-to-methylene carbon thioether bond formation in QhpC bound to QhpD, producing a multiknotted structure of the polypeptide chain. Homology modeling and mutagenic analysis revealed several conserved residues indispensable for both in vivo and in vitro activities of QhpD. Our findings uncover another challenging reaction catalyzed by a radical SAM enzyme acting on a ribosomally translated protein substrate.
Keywords: Bacterial Proteins; oxidoreduktasy; proteiny obsahující železo a síru; Electron Spin Resonance Spectroscopy; Paracoccus denitrificans; Iron-Sulfur Proteins; elektronová paramagnetická rezonance; Oxidoreductases; bakteriální proteiny